COMPARATIVE STUDY OF MODAL RESPONSE BETWEEN FINITE ELEMENT AND DYNAMIC STIFFNESS METHODS OF PLANE FRAME STRUCTURES - Essen (NIM 250 05 013), Donald
Abstract : Modal analysis is the most critical phase in dynamic analyis. Many structural analysis nowadays are employed using programs that based on finite element method which is discrete method. Because of that, mass can only be represented in structural nodes and in order to get a continuos mass distribution on structure, structural members must be divided into a theoretically infinite number of smaller elements. Modal response of beam and plane frame structures has been analyzed to study its sensitivity to the finite element discretizations and has been compared to the results from dynamic stiffness method. It is observed that in beam structures, the use of 3xN elements as minimum number of element to get an accurate modal response where N is the mode being considered is only correct for natural frequency but not for modal participation factor or modal displacement. Thus for beam structure, it is suggested to divide the beam into many smaller elements as possible so the modal response can be calculated accurately. For plane frame structures, it is obtained that the number of element mesh is decreasing with the increase of beam to column mass ratio and with respect to symmetric-regular plane frame structures excited by horizontal earthquake load, no mesh is needed even though the accuracy of modal response might be decreasing with the increase of number of modes being considered. For unsymmetric-irregular frames with and without shearwalls, analysis result shows that for fundamental mode and few lower modes, modal responses being calculated are accurate enough without mesh but not for higher sidesway modes. The complexity of vibration modes and mesh problem in vibration analysis of unsymmetirc-irregular structure using finite element method shows the importance of building structures to posses as possible, a symmetric and regular configuration.